Characterisation of the interaction between WRN, the helicase/exonuclease defective in progeroid Werner's syndrome, and an essential replication factor, PCNA. - Rodríguez-López, A; Jackson, D; Nehlin, J; Iborra, F; Warren, A; Cox, L (2003)
Ageing is linked to the accumulation of replicatively senescent cells. The best model system to date for studying human cellular ageing is the progeroid Werner's syndrome (WS), caused by a defect in WRN, a recQ-like helicase that also possesses exonuclease activity. In this paper, we characterise the interaction between WRN and an essential replication factor, PCNA. We show that wild-type WRN protein physically associates with PCNA at physiological protein concentrations in normal cells, while no association is seen in cells from patients with WS. We demonstrate co-localisation of WRN and PCNA at replication factories, show that PCNA binds to two distinct functional sites on WRN, and suggest a mechanism by which association between WRN and PCNA may be regulated in cells on DNA damage and during DNA replication.